Literacy among Young People and Adults - Flores-Davis, Luz Emilia (2015)
This article aims to share experiences and reflections carried out during over twenty years of working in the literacy issue among young people and adults, as well as offering ideas that can foster new experiences. Literacy among adults is a practice of coexistence where both the mediator and the student learn. Each literacy learning mediation exercise is unique; therefore the path to the proper name shared here must be contextualized. The basic premises which are developed in this article have to do with the right of every person to learn how to read and write his/her own reality, depicted from their circumstances and dreams; in other words, from their experiences, ideas, expertise, feelings and hopes. The latter involves locating the learner person as the center of the learning process and, hence, respecting his/her interests, needs and learning pace.